N-terminal region of Drosophila melanogaster Argonaute2 forms amyloid-like aggregates - Narita, Haruka; Shima, Tomohiro; Iizuka, Ryo; Uemura, Sotaro (BMC biology, 2023)
Argonaute proteins play a central role in RNA silencing by forming protein-small RNA complexes responsible for the silencing process. While most Argonaute proteins have a short N-terminal region, Argonaute2 in Drosophila melanogaster (DmAgo2) harbors a long and unique N-terminal region. Previous in vitro biochemical studies have shown that the loss of this region does not impair the RNA silencing activity of the complex. However, an N-terminal mutant of Drosophila melanogaster has demonstrated abnormal RNA silencing activity. To explore the causes of this discrepancy between in vitro and in vivo studies, we investigated the biophysical properties of the region. The N-terminal region is highly rich in glutamine and glycine residues, which is a well-known property for prion-like domains, a subclass of amyloid-forming peptides. Therefore, the possibility of the N-terminal region functioning as an amyloid was tested. Our in silico and biochemical assays demonstrated that the N-terminal region exhibits amyloid-specific properties. The region indeed formed aggregates that were not dissociated even in the presence of sodium dodecyl sulfate. Also, the aggregates enhanced the fluorescence intensity of thioflavin-T, an amyloid detection reagent. The kinetics of the aggregation followed that of typical amyloid formation exhibiting self-propagating activity. Furthermore, we directly visualized the aggregation process of the N-terminal region under fluorescence microscopy and found that the aggregations took fractal or fibril shapes. Together, the results indicate that the N-terminal region can form amyloid-like aggregates. Many other amyloid-forming peptides have been reported to modulate the function of proteins through their aggregation. Therefore, our findings raise the possibility that aggregation of the N-terminal region regulates the RNA silencing activity of DmAgo2.